(untitled) (Conferencea, 2022)
This article talks about the state of housing policy in Uzbekistan. The author relied on economic data as well as scientific sources and made clarifications on the basis of available literature. He made a comparative analysis of existing approaches and theories on the state of residential policy in Uzbekistan.